Review of the Theoretical Description of Time‐Resolved Angle‐Resolved Photoemission Spectroscopy in Electron‐Phonon Mediated Superconductors. Issue 9 (13th July 2017) - Kemper, A. F.; Sentef, M. A.; Moritz, B.; Devereaux, T. P.; Freericks, J. K.
Abstract : This paper reviews work on nonequilibrum dynamical mean‐field theory for superconductors emphasizing different phenomena that can be observed in photoemission. Abstract: We review recent work on the theory for pump/probe photoemission spectroscopy of electron‐phonon mediated superconductors in both the normal and the superconducting states. We describe the formal developments that allow one to solve the Migdal‐Eliashberg theory in nonequilibrium for an ultrashort laser pumping field, and explore the solutions which illustrate the relaxation as energy is transferred from electrons to phonons. We focus on exact results emanating from sum rules and approximate numerical results which describe rules of thumb for relaxation processes. In addition, in the superconducting state, we describe how Anderson‐Higgs oscillations can be excited due to the nonlinear coupling with the electric field and describe mechanisms where pumping the system enhances superconductivity.